Longitudinal health-related quality of life in patients with pancreatic cancer stratified by treatment: a nationwide cohort studyResearch in context - Anne M. Gehrels; Pauline A.J. Vissers; Mirjam A.G. Sprangers; Nienke M. Fijnheer; Esther N. Pijnappel; Lydia G. van der Geest; Geert A. Cirkel; Judith de Vos-Geelen; Marjolein Y.V. Homs; Geert- Jan Creemers; Martijn W.J. Stommel; Lois A. Daamen; et al. (EClinicalMedicine)
Summary: Background: Pancreatic adenocarcinoma (PAC) has a poor prognosis and substantially impairs health-related quality of life (HRQoL). Large studies on longitudinal HRQoL in patients with PAC, taking patient treatment into account, are lacking. This study aimed to investigate HRQoL over time in patients with PAC undergoing various treatments. Methods: This nationwide cohort study included patients diagnosed with PAC between 2015 and 2020. Data were collected from the Dutch Pancreatic Cancer Project (PACAP) and the Netherlands Cancer Registry. Patients were categorized into four groups based on treatment modality: resection (R-PAC), chemotherapy for localized disease (C-PAC), chemotherapy for metastatic disease (M1-C-PAC), and best supportive care (BSC). HRQoL was assessed using the EORTC QLQ-C30 and -PAN26 questionnaires at baseline, during treatment, and at 0–3 months and 3–6 months after treatment. Linear mixed models were used to analyze changes in HRQoL over time, with clinically relevant changes defined as a minimal mean difference of 10 points in absolute scores and reported with 95% confidence intervals. Findings: Overall, 1496 patients were included (673 [45.0%] female), of whom 675 (45.1%) in R-PAC, 319 (21.3%) in C-PAC, 340 patients (22.7%) in M1-C-PAC, and 162 (10.8%) in BSC group. In R-PAC, hepatic symptoms and health care satisfaction improved while role and social functioning deteriorated and eating related problems, side effects and fear of future health increased during treatment. In C-PAC, insomnia, pancreatic pain, hepatic symptoms decreased while diarrhea, side effects and fear of future health increased. In M1-C-PAC, pain, insomnia, pancreatic pain, hepatic symptoms, ascites and constipation decreased, sexuality improved while fear of future health and side effects increased. In BSC, hepatic symptoms decreased and flatulence increased. Interpretation: This nationwide study identified specific improvements and deteriorations in various HRQoL domains during 6 months follow-up. This information may be valuable in the clinical setting to inform patients on potential outcomes of the course of HRQoL during various treatment strategies. Funding: None.